Analysis and characterization of microplastic from personal care products and surface water in Bangi, Selangor - Nur Hapizah Suardy; Nurfaizah Abu Tahrim; Suria Ramli (Penerbit Universiti Kebangsaan Malaysia, 2020)
Primary microplastics which include microbeads are added into cosmetics and personal care products as scrubbing agent and mostly used because of their uniformity and effective exfoliating properties. However due to their small size, microplastic cannot be filtered by the water treatment plant and flow into our waterways posing a great threat to the aquatic life. Therefore, this study aims to detect the presence of microplastics in personal care products and surface water. Microplastic from personal care samples were extracted using warm water at 60 ⁰C and then characterized using ATR - FTIR to determine the polymer composition. Based on the spectrum, the extracted microplastics were confirmed as polyethylene with significance peaks at 2800 - 2900 cm-1 (C-H stretching) and medium band at 700 cm-1 which indicates the presence of ethylene networks. The extracted microplastics were also identified as polystyrene with the important peaks appear at 3300 and 1600 cm-1 with additional weak peak at 1400 cm-1 which represent C-H aromatic stretching and C=C aromatic group, respectively. Next, SEM method was used to determine the morphology and size of the microplastics which give sizes ranging from 200-500 µm for each sample. Furthermore, optical microscope was used to determine the color and shape of the microbeads. The results showed that extracted microbeads come from various colors such as white, purple, pink, brown and colorless while the shape observed was spherical, granular, and irregular. Next, insect net and bucket techniques were used in sampling of surface water. The successfully filtered solids were analysed using WPO method and characterize by ATR-FTIR technique. The microplastics found in surface water sample were from various shape including fragment, film, pellet, foam, and tube with the majority come from PE type polymer plastic. Hence, this study proved the presence of microplastic in personal care products that available in Malaysia as well as in surface water.